Nonimmune antibody interactions of Group A Streptococcus M and M-like proteins. - Jori O Mills (Public Library of Science (PLoS), 2021)
M and M-like proteins are major virulence factors of the widespread and potentially deadly bacterial pathogen Streptococcus pyogenes. These proteins confer resistance against innate and adaptive immune responses by recruiting specific human proteins to the streptococcal surface. Nonimmune recruitment of immunoglobulins G (IgG) and A (IgA) through their fragment crystallizable (Fc) domains by M and M-like proteins was described almost 40 years ago, but its impact on virulence remains unresolved. These interactions have been suggested to be consequential under immune conditions at mucosal surfaces and in secretions but not in plasma, while other evidence suggests importance in evading phagocytic killing in nonimmune blood. Recently, an indirect effect of Fc-binding through ligand-induced stabilization of an M-like protein was shown to increase virulence. Nonimmune recruitment has also been seen to contribute to tissue damage in animal models of autoimmune diseases triggered by S. pyogenes infection. The damage was treatable by targeting Fc-binding. This and other potential therapeutic applications warrant renewed attention to Fc-binding by M and M-like proteins.